Divya-Arjuna-Kwath (Terminalia arjuna) and Divya-HridyAmrit-Vati ameliorate isoproterenol-induced hypertrophy in murine cardiomyocytes through modulation of oxidative stress - Acharya Balkrishna; Yashika Rustagi; Meenu Tomer; Subarna Pokhrel; Kunal Bhattacharya; Anurag Varshney (Elsevier, 2021)
Background: Pathological stress can lead to the development of cardiac hypertrophy (CH) through induction of oxidative stress and tissue remodeling. Initiation of CH is associated with increase in cardiac myocyte size, generation of reactive oxygen species and expressional changes in fetal cardiac genes. Ayurveda has prescribed several herbo-mineral formulations that can benefit during cardiac morbidities, including CH. Purpose: In this study, we analyzed the efficacy of traditional Ayurveda-based medicines Divya-Arjuna-Kwath (bark extract of Terminalia arjuna; TAE), and Divya-HridyAmrit-Vati (HAV) in attenuating Isoproterenol (ISP)-stimulated CH in murine cardiomyocytes (H9c2). Methods: H9c2 cells were exposed to varying concentrations of ISP, TAE and HAV for cytosafety assessment. An inhibition concentration of 50% for ISP was observed at 145.2 µM in H9c2 cells. H9c2 cells were stimulated with 50 µM of ISP and studied for the CH-modulating efficacy of TAE and HAV at cellular, biochemical, and molecular levels. Results: ISP-induced CH in H9c2 cells through an increase in cellular protein content, cell size increase, escalation in intracellular reactive oxygen species (ROS) generation, mitochondrial membrane potential (MMP), and reduced antioxidant levels. ISP-stimulated an over-expression of CH-biomarker genes for oxidative stress (LOX-1, COX-2, NOX-2, and NOX-4), fetal cardiac remodeling (ACTC-1, and ANF), and cardiac injury (TNNI, TNNT, and CRLS-1). Co-treatment of ISP-stimulated H9c2 cells with TAE or HAV modulated the cellular redox state through inhibition of ROS, MMP, and rebalancing antioxidant levels. TAE and HAV reduced the over-expression of ISP-stimulated CH-biomarker genes in H9c2 cells. HPLC-based phytochemicals analysis of TAE and HAV showed the presence of ellagic acid, quercetin, catechin, gallocatechin, arjunic acid, arjungenin, gallic acid, and vanillic acid reported to have antioxidant properties. Conclusion: Taken together, Divya-Arjuna-Kwath and Divya-HridyAmrit-Vati showed substantial pharmacological effects in the intonation of ISP-stimulated oxidative stress in the H9c2 cardiomyocytes; and could be considered as the complementary Ayurveda-based formulation for curing cardiac ailments like hypertrophy.